ANALISIS PENGARUH RASIO LIKUIDITAS, RASIO LEVERAGE, DAN RASIO AKTIVITAS TERHADAP KINERJA KEUANGAN PERUSAHAAN PADA PERUSAHAAN FOOD AND BEVERAGES YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2009-2013 - Xaveria Turnip, 11.05.52.0108; Srimindarti, Ceacilia (Students Journal of Accounting and Banking, 2015)
The research purpose to exanine the effect of liquidity ratio, leverage ratio and ratio of activity on financial performance with signal theory perspective. The independent variable in this research is current ratio, debt to equity ratio, total assets turnover and inventory turnover. Return on investment is one of indicators which used to assessing the financial performance company. The relation between the current ratio, debt to equity ratio, total assets turnover, and inventory turnover expected to help the investors see the good or the bad of companyâs financial performance. So that it can influence the desicions that will be taken by the investors. The population in this research there are 94 food and beverage companies which with this research take sample by using purposive sampling method. So as to obtain 89 samples data. This research is free from normality test and classical assumption. The result of this research indicate that the current ratio significant possitive effect on return on investment, debt to equity ratio has significant possitive effect on return on investment, total assets turnover has significant possitive effect on return on investment, and inventory turnover has significant possitive effect on return on investment. Keywords: Current Ratio, Debt to Equity Ratio, Total Assets Turnover, Inventory Turnover and Financial Performance Company